2009
DOI: 10.1152/ajpheart.01185.2008
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy modifies the large conductance Ca2+-activated K+ channel and cGMP-dependent signaling pathway in uterine vascular smooth muscle

Abstract: Regulation of uteroplacental blood flow (UPBF) during pregnancy remains unclear. Large conductance, Ca(2+)-activated K(+) channels (BK(Ca)), consisting of alpha- and regulatory beta-subunits, are expressed in uterine vascular smooth muscle (UVSM) and contribute to the maintenance of UPBF in the last third of ovine pregnancy, but their expression pattern and activation pathways are unclear. We examined BK(Ca) subunit expression, the cGMP-dependent signaling pathway, and the functional role of BK(Ca) in uterine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
91
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(97 citation statements)
references
References 56 publications
5
91
1
Order By: Relevance
“…While it is clear that NO contributes to basal UPBF regulation, it is not the primary pathway, confirming earlier reports (27,35). We and others (13,34,38) have shown that large-conductance Ca 2ϩ -activated K ϩ (BK Ca ) channels are major contributors to the maintenance of basal ovine UPBF; e.g., unilateral BK Ca channel inhibition decreases basal UPBF Ն80% without affecting the noninfused uterine horn or cGMP synthesis. BK Ca channel activation occurs via the NOS-NO-cGMP-PKG pathway and/or direct activation by estrogens via the ␤ 1 -regulatory subunit, which is upregulated in the UA during the last third of ovine pregnancy (8,9,41,50).…”
Section: Discussionsupporting
confidence: 86%
“…While it is clear that NO contributes to basal UPBF regulation, it is not the primary pathway, confirming earlier reports (27,35). We and others (13,34,38) have shown that large-conductance Ca 2ϩ -activated K ϩ (BK Ca ) channels are major contributors to the maintenance of basal ovine UPBF; e.g., unilateral BK Ca channel inhibition decreases basal UPBF Ն80% without affecting the noninfused uterine horn or cGMP synthesis. BK Ca channel activation occurs via the NOS-NO-cGMP-PKG pathway and/or direct activation by estrogens via the ␤ 1 -regulatory subunit, which is upregulated in the UA during the last third of ovine pregnancy (8,9,41,50).…”
Section: Discussionsupporting
confidence: 86%
“…There also may be differences in the expression and/or function of vascular smooth muscle K ϩ channels that contribute to myogenic responses and have been identified in the uteroplacental circulation, e.g., K v and BK Ca (32,39,43,50). These channels have been identified in women (43), sheep (37), and rat (41,50) uterine arteries and shown to modify maternal uterine blood flow (18,42), but their expression and function in human MA is not known. Whereas BK Ca channels appear to modulate uterine vasodilation and vasoconstriction in women and sheep (39,41,43), downregulation and/or inactivation of K v channels is associated with increased myogenic responses in small uterine arteries from pregnant rats (50).…”
Section: Discussionmentioning
confidence: 99%
“…38). In contrast, endothelium-derived hyperpolarizing factor (83,86,114,123,124,126,164,175), K ATP ϩ channel activation (100) and endothelium-derived relaxing factor (EDRF) or nitric oxide (NO) (175) autocoid was implicated in the vasodilatory phenomena of pregnancy (28,43). Later, evidence for increased NO biosynthesis was reported in gravid rats (37).…”
Section: Molecular Mechanisms Of Renal Vasodilation In Pregnancymentioning
confidence: 99%